Returns - Dent, Gina (Columbia Journal of Gender and Law, 2014)
Patricia Williams was my teacher. In the five stages of preparing for this day, I heard many of the phrases from The Alchemy of Race and Rights echo through my mind. I felt just like that monkey Williams describes staring at the keyboard, as she puts it, “all those letters of the alphabet, full of random signification.” And, of course, there was no shortage of news items vying for my attention on radio and TV. George Zimmerman’s brother, Robert, was interviewed by Michael Martin on NPR’s Tell Me More, explaining why growing up with his Afro-Peruvian mother in Virginia meant that race could not be a factor in his brother’s shooting of Trayvon Martin in Florida one year ago, their growing-up marked, as it was, by a difference of culture (of foods and how they spoke at home, he mentioned), while also ensuring, he suggested, his family’s color blindness. The President of Emory University wrote confidently about the Three-Fifths Compromise as an historical example that might be useful in fending off the contemporary threat of sequester, avoiding the fiscal cliff, and getting the President and Congress (the only relevant social actors) to work together. In his response to criticism about his letter, he went on to apologize for the “hurt caused by not communicating more clearly [his] own beliefs.” And the State of Mississippi’s attempt to get rid of the sole abortion clinic remaining in the state through House Bill 1390, ostensibly making Mississippi an “abortion-free” state, as Governor Phil Bryant called it, could only recall Williams’ prescient words: “[T]he right to privacy might be a function of wealth.”